Analysis of part jamming in a feeder of automatic machines - Ryspek, Usubamatov, Prof. Dr.; A., Usubamatova; Mohd Zaki, Ab Muin, Porf. Dr. (Emerald Group Publishing Limited, 2011)
Link to publisher's homepage at http://www.emeraldinsight.com/